Effect of homogenization in breaking protein-carotenoid complexes for releasing active compounds - Jamal, Parveen; Jaswir, Irwandi; Hashim, Nurhasri Mulyadi; Azmi, Saiful Mohammad Nizam (IIUM Press, 2011)
The effect of homogenization in breaking protein-carotenoid complexes from cassava leaves was examined by monitoring three process conditions; amount of solvent per 0.5 g sample (ml), homogenization speed (rpm) and homogenization time (s). Acetone-n-hexane (1:1, v/v), tetrahydrofuran-methanol (1:1 v/v) and acetone were employed in the extraction process. The solvent that exhibited the best characteristics in extracting the highest b-carotene yield from the sample was selected for the optimizatIOn of process conditions for maximum b-carotene concentration, utilizing Face Centered Central Composite Design (FCCD) from Design Expert software, version 6 (DX6). A total of 20 experiments comprised of three factors, three levels and 6 center points were conducted to facilitate the optimization process. The maximum b-carotene yield of 17,544 flg/lOO g sample was achieved with the solvent ratio of 12 ml to 0.5 g sample, homogenization speed of 22000 rpm and homogemzation time of 57 s.